Defective Mitophagy Impairs Response to Inflammatory Activation of Macrophage-Like Cells - Orekhov, Alexander Nikolaevich; Zhuravlev, Alexander Dmitrievich; Vinokurov, Andrey Yurievich; Nikiforov, Nikita Gennadievich; Omelchenko, Andrey Vladimirovich; Sukhorukov, Vasily Nikolaevich; Sinyov, Vasily Vladimirovich; Sobenin, Igor Alexandrovich (Current Medicinal Chemistry, 2025)
Background and AimsThe role of mitophagy in atherosclerosis has been extensively studied during the last few years. It was shown that mitophagy is involved in the regulation of macrophages, which are important players as immune cells in atherosclerosis development. In this study, we investigated the relationship between mitophagy and response to inflammatory stimulation of macrophage-like cells. Six cybrid cell lines with normal mitophagy, that is, increasing in response to stimulation, and 7 lines with defective mitophagy not responding to stimulation were obtained. The objective of the study was to compare the nature of the inflammatory response in normal and defective mitophagy in order to elucidate the role of mitophagy defects in inflammation.MethodsWe used cytoplasmic hybrids (cybrids) as cellular models, created using mitochondrial DNA from different atherosclerosis patients. Mitophagy was stimulated by carbonyl cyanide m-chlorophenyl hydrazone (CCCP) and assessed as the degree of colocalization of mitochondria with lysosomes using confocal microscopy. Western blotting methods were used for the determination of proteins involved in the exact mechanism of mitophagy. Experiments with stimulation of mitophagy show a high correlation between these two approaches (microscopy and blotting). The pro-inflammatory response of cybrids was stimulated with bacterial lipopolysaccharide (LPS). The extent of the inflammatory response was assessed by the secretion of cytokines CCL2, IL8, IL6, IL1β, and TNF measured by ELISA.ResultsBasal level of secretion of cytokines CCL2, IL8 and TNF was 1.5-2 times higher in cultures of cybrids with defective mitophagy compared to cells with normal mitophagy. This suggests a persistently elevated inflammatory response in cells with defective mitophagy, even in the absence of an inflammatory stimulus. Such cells in the tissue will constantly recruit other immune cells, which is characteristic of macrophages derived from monocytes circulating in the blood of patients with atherosclerosis. We observed significant differences in the degree and type of response to inflammatory activation in cybrids with defective mitophagy. These differences were not so much quantitative as they were dramatically qualitative. Compared with cells with normal mitophagy, in cells with defective mitophagy, the relative (to basal) secretion of IL8, IL6 and IL1b increased after the second LPS activation. This indicates a possible lack of tolerance to inflammatory activation in cells with defective mitophagy, since typically, re-activation reveals a smaller pro-inflammatory cytokine response, allowing the inflammatory process to resolve. In cells with normal mitophagy, exactly this normal (tolerant) inflammatory reaction was observed.ConclusionData on the involvement of mitophagy, including defective mitophagy, in disturbances of the inflammatory response in sepsis, viral infections, autoimmune diseases and other pathologies have previously been reported. In this work, we studied the role of defective mitophagy in non-infectious chronic inflammatory diseases using the example of atherosclerosis. We showed a dramatic disruption of the inflammatory response associated with defective mitophagy. Compared with cybrids with normal mitophagy, in cybrids with defective mitophagy, the secretion of all studied cytokines changed significantly both quantitatively and qualitatively. In particular, the secretion of 3 of 5 cytokines demonstrated an intolerant inflammatory response manifested by increased secretion after repeated inflammatory stimulation. Such an intolerant reaction likely indicates a significant disruption of the pro-inflammatory response of macrophages, which can contribute to the chronification of inflammation. Elucidating the mechanisms of chronification of inflammation is extremely important for the search for fundamentally new pharmacological targets and the development of drugs for the prevention and treatment of chronic inflammatory diseases, including atherosclerosis and diseases characteristic of inflammation. Such diseases account for up to 80% of morbidity and mortality.
Keywords: chronification of inflammation